PENGARUH STRUKTUR KEPEMILIKAN MANAGERIAL, INSTITUSIONAL DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR SEKTOR KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ade Fernando; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to partially and simultaneously influence. Managerial, Institutional Ownership, and Profitability to Debt Policy. Where independent variable in this research is rival managerial, institutional, and profitability dependent variable. The sample used is secondary data derived from the financial statements of Chemical Manufacturing Companies Listed on Indonesia Stock Exchange(BEI) Period 2009-2014. Samples were taken by purposive sampling and samples that met the selection criteria. Sample used as many as 5 companies.Based on the results of t test that compares the value of t tables obtained for 2.055 with t arithmetic or p value with α (0.05). Lacking the results of managerial scope is not biased against the debt policy on the sample company. This is evidenced by the value of t arithmetic of -1.285 and p value 0.201. Negative and significant institutional ownership of debt policy in sample companies. Evidenced by the value of t arithmetic of -2.188 and p value 0.038. Profitability and negative towards. Evidenced by the value of t arithmetic of -3.379 and p value 0.002.Based on F test results that compare the value of f table can be as much as 2.96 with F arithmetic or Pvalue with α (0,05). Simultaneous results between Managerial, Institutional Ownership, and Profitability to Debt Policy at sample company, This is evidenced by the value of F count of 6.846 and p value of 0.005.Keywords : managerial ownership, institutional institution, profitability, debt policy